176k views
4 votes
What is the reason for each step in the solution of the equation?

19=5x−1

User Krakkos
by
6.1k points

1 Answer

3 votes

2x = -4(x-3) now we will use: distributive property

2x=-4x + 12 we will use: addition property of equality

6x=12 at the end we use: division property of equality


first we used distributive property to get rid of brackets. After that we used addition property of equality where we added 4x to each sides. Finally we used division property of equality where we divided each side by 6.

User Kush Bhavsar
by
5.8k points